Pembuatan Aplikasi Sistem Informasi Akuntasi Pada CV. Sablon Makmur - Andry Hartanto; Djoni Haryadi; Rudy Adipranata (Jurnal Infra, 2016)
CV. Sablon Makmur is a company engaged in screen printing services. The company's current systems still using manual systems. All recording report purchases, sales, bookkeeping still use hand writing, so it's easy errors in the registration process. Calculation of benefits are still estimated, the company also made sometimes difficulties in calculating benefits.Based on the analysis of the problems faced by CV. Sablon Makmur, then made the creation of applications that are useful for operations. Applications can implement transaction processing purchase orders, sales orders, purchasing reports, sales, accounts payable and receivable, so that the company can manage its report. Data Flow Diagram and ERD using power applications designer 15. Applications created using CodeIgniter Framework and uses MySQL as a database.Based on the test results of the application indicates that this application can make record purchase and sale transactions in a structured and automated, and equipped with a calculation of the stock using the Average. This application helps the process of recording with journaling and posting of computerized and automated